PEMEROLEHAN BAHASA PADA ANAK USIA 3 TAHUN BERDASARKAN ASPEK MORFOLOGI - Ranzella Susmitha; Yulia Sri Hartati; Febrina Riska Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Language acquisition is a complex process that occurs naturally in children from an early age, especially in the morphological aspect which includes the formation and use of words. This study aims to explain how morphological acquisition, especially the affixation process, occurs in 3-year-old children. The subject in this study was Rayyanza Malik Ahmad, the son of public figures Raffi Ahmad and Nagita Slavina. Rayyanza's age, which is now 3 years old, is considered a crucial phase in language development, where children begin to master morphological forms such as prefixes, suffixes, and confixes. This type of research is qualitative research. The method used in this study is a descriptive method. The data for this study are utterances containing affixation sentences delivered by the research subjects and data sources come from 20 videos with a duration of 10 to 25 minutes in each video. The main instrument is the researcher himself. Data collection techniques are recording techniques and free listening techniques. This study shows that Rayyanza's morphological acquisition occurs faster than the average child his age. He has been able to use complex word forms and compound sentences, which are generally only mastered by children aged 4–5 years. The speed of this acquisition is influenced by several factors, including: a supportive and communicative family environment, active social interaction, use of media and technology, supportive social status, and good intelligence and cognitive abilities. Exposure to rich language in various real-life contexts also accelerated the process of acquiring affixation in Rayyanza.